Aplicación de balanced scorecard en el proceso de gestión de la empresa procesos textiles e.i.r.l. - Mendoza Zuta, Jannie Caroll (2016)
This research work has been developed and implemented the Balanced ScoreCard (BSC) as a management model, a tool that allows measurement and management control of the areas considered critical, which is a pilot applicable later to the entire organization, in order to improve profitability and optimization of the same. The Deductive method used in this research, specifically the pre-experimental method with pre and post- test to determine the managing before and after applying the Balanced ScoreCard, which was developed on the base of the Balanced ScoreCard theories, planning and control; Initially, a study of the current situation of both internal company and its market share, critical environmental factors and critical success factors was conducted. And with all of this, we designed and analyzed the SWOT (strengths, weaknesses, opportunities and threats) to determine the objectives and strategies. Based on this analysis, the Balanced Scorecard and then identify indicators in each perspective of the BSC was designed. The Application of Balanced Scorecard had as a result an increase in net profit 4.10 % (compared to 2014 and 2013) and the measurement and control of each perspective optimizing the results in each; it still has the limitation that the improvements in the implementation of the BSC are reflected from August 2014. Therefore, we can conclude that If applied throughout the year, the results would be better.